Effect of charge ordering and phase separation on the electrical and magnetoresistive properties of polycrystalline La0.4Eu0.1Ca0.5MnO3. (March 2018) - Krichene, A.; Boujelben, W.; Mukherjee, S.; Shah, N.A.; Solanki, P.S.
Abstract: We have investigated the effect of charge ordering and phase separation on the electrical and magnetotransport properties of La0.4 Eu0.1 Ca0.5 MnO3 polycrystalline sample. Temperature dependence of resistivity shows a metal–insulator transition at transition temperature T ρ . A hysteretic behavior is observed for zero field resistivity curves with T ρ  = 128 K on cooling process and T ρ  = 136 K on warming process. Zero field resistivity curves follow Zener polynomial law in the metallic phase with unusual n exponent value ∼9. Presence of resistivity minimum at low temperatures has been ascribed to the coulombic electron–electron scattering process. Resistivity modification due to the magnetic field cycling testifies the presence of the training effect. Magnetization and resistivity appear to be highly correlated. Magnetoresistive study reveals colossal values of negative magnetoresistance reaching about 75% at 132 K under only 2T applied field. Colossal values of magnetoresistance suggest the possibility of using this sample for magnetic field sensing and spintronic applications. Graphical abstract: Highlights: La0.4 Eu0.1 Ca0.5 MnO3 polycrystalline sample is characterized by phase separation, charge ordering and training effect. Around 75% of colossal magnetoresistance was recorded in vicinity of 132 K for only 2T magnetic field. Resistivity exhibits an unusual upturn at very low temperature. Strong correlation between electrical and magnetic properties was detected.